2024
DOI: 10.1111/ijac.14675
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the structural and photocatalytic performance of Ag‐decorated ZnO/Zn(OH)2 nanoparticles for RhB degradation

Erman Erdogan,
Cigdem Eden,
Nurtac Canpolat
et al.

Abstract: In this study, as‐prepared and Ag‐decorated ZnO/Zn(OH)2 composite nanoparticles (NPs) were obtained using the sol–gel technique. First, the effect of aging on the structural, optical, and morphological features was examined. Ag NPs can interact with the electronic structure of ZnO/Zn(OH)2 NPs, resulting in changes in their energy levels. It was found that the composite NPs obtained after 6 h solution aging increased in full width at half maximum and good crystallinity of the structures from the X‐ray diffracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…As shown in Figure 3 b, Fe 3 O 4 /ZnO displays three apparent peaks. The broad absorption band in the range of 3000~3500 cm −1 corresponds to the O-H stretching vibrations of adsorbed water and hydroxyl groups in the samples [ 22 , 25 , 27 ]. In the 1000 to 1600 cm −1 region, the absorption band at ~1633 cm −1 is attributed to the C=O stretching vibration of carboxylic organic acids or the bending vibration of O-H bonds from H 2 O molecules [ 25 , 27 , 29 ], due to the use of zinc acetate, sodium citrate, and sodium hydroxide.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 3 b, Fe 3 O 4 /ZnO displays three apparent peaks. The broad absorption band in the range of 3000~3500 cm −1 corresponds to the O-H stretching vibrations of adsorbed water and hydroxyl groups in the samples [ 22 , 25 , 27 ]. In the 1000 to 1600 cm −1 region, the absorption band at ~1633 cm −1 is attributed to the C=O stretching vibration of carboxylic organic acids or the bending vibration of O-H bonds from H 2 O molecules [ 25 , 27 , 29 ], due to the use of zinc acetate, sodium citrate, and sodium hydroxide.…”
Section: Resultsmentioning
confidence: 99%
“…The broad absorption band in the range of 3000~3500 cm −1 corresponds to the O-H stretching vibrations of adsorbed water and hydroxyl groups in the samples [ 22 , 25 , 27 ]. In the 1000 to 1600 cm −1 region, the absorption band at ~1633 cm −1 is attributed to the C=O stretching vibration of carboxylic organic acids or the bending vibration of O-H bonds from H 2 O molecules [ 25 , 27 , 29 ], due to the use of zinc acetate, sodium citrate, and sodium hydroxide. It also revealed that a few hydroxide radicals were adsorbed on the surface of the composite material, which would make a contribution to high photocatalytic performance for RhB degradation by facilitating the generation of active ·OH radicals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation